PF.69 Ireland's National Perinatal Neurosurgical Clinic: Referral Patterns and Outcomes, 2010–2012. (26th April 2013) - Walsh, CA; McAuliffe, FM; Crimmins, D; Laffan, E; Donoghue, V; Higgins, S; Mahony, R; Carroll, S; McParland, P
Abstract : Background: Anomalies of the fetal central nervous system (CNS) require considerable expertise. In 2010 we launched a Perinatal Neurosurgical Clinic, wherein fetal CNS anomalies are assessed and counselled by a multi-disciplinary team, comprising a fetal medicine specialist, a paediatric neurosurgeon, a paediatric radiologist and a specialist nurse. Materials and Methods: A prospective review of all patients referred to our clinic from Jan 2010 to July 2012. All cases were triaged initially by a fetal medicine specialist to confirm diagnosis. If warranted, a fetal MRI was obtained prior to referral. Individual patient records were examined to determine pregnancy outcome. Results: Over the study period, 122 fetal CNS anomalies (excluding choroid plexus cysts) were seen. Of these, 41 women (34%) were referred to the Neurosurgical Clinic, including 1 case each of caudal regression syndrome, neuronal migration disorder, sacrococcygeal teratoma, AV malformation, agenesis corpus callosum, cerebellar hypoplasia and thoracolumbar gibbus ( Table ). Median gestation at referral was 30.5 weeks. Three women opted for termination. Of the remaining cases, 53% underwent fetal MRI. In 35%, MRI was considered to alter the diagnosis and counselling. 60% of women underwent caesarean delivery, at a median 38.8 weeks. Excluding 3 cases of holoprosencephaly, the perinatal mortality rate in this high risk cohort was 0%. Conclusion: A multi-disciplinary Perinatal Neurosurgical Clinic offers excellent potential, both in expert management of common CNS anomalies, such as neural tube defects, and in the assessment of much rarer fetal CNS anomalies.